Presence of Anti-Thyroid Antibodies Correlate to Worse Outcome of Anti-NMDAR Encephalitis - Chen, Zhongyun; Zhang, Yan; Cui, Lili; Huang, Huijin; Chen, Weibi; Su, Yingying (Frontiers in Immunology, 2021)
Objective: To investigate the characteristics and prognosis of anti-NMDAR encephalitis with the prevalence of anti-thyroid antibodies (ATAbs). Methods: The clinical data of anti-NMDAR encephalitis patients admitted to Xuanwu Hospital from January 2012 to August 2018 was prospectively analyzed, and the patients were followed up for 24 months. Results: A total of 120 patients were enrolled, of which 34.2% (41/120) were positive for ATAbs. The antibodies were more frequent in patients with severe disease compared to the non-severe group (51.4% vs. 25.6%, P=0.008). In addition, prevalence of ATAbs correlated with a higher incidence of disturbed consciousness, autonomic dysfunction, central hypoventilation and mechanical ventilation. The ATAbs-positive patients were also more likely to receive intravenous gamma immunoglobulin and immunosuppressor compared to the ATAbs-negative cases (P=0.006; P=0.035). Although the presence of ATAbs was associated with longer hospital stays and worse prognosis at 6 months (P=0.006; P=0.038), it had no impact on long-term patient prognosis. Positive status of anti-thyroglobulin antibody was an independent risk factor for worse prognosis at 6 months [odds ratio (OR)=3.401, 95% CI: 1.084-10.672, P=0.036]. Conclusion: ATAbs are prevalent in patients with anti-NMDAR encephalitis, especially in severe cases, and correlate with poor prognosis and impaired short-term neurological recovery.